Determination of Immune Related Haemato-biochemical Parameters of Native Chicken of Himachal Pradesh and Comparison with Dahlem Red Breed - Saklani, Smriti (ISVIB Journal Veterinary Immunology & Biotechnology, 2019)
Native chickens are the important part of the free range and scavenging poultry production of rural areas of the Himachal Pradesh. The knowledge of baseline values of immune related haemato-biochemical parameters under local conditions is essential. Thus, haematological parameters such as heterophil, lymphocyte, basophil, eosinophil and monocyte counts and biochemical parameters such as plasma total proteins, albumin and globulin for native chicken of Himachal Pradesh were estimated and compared with the exotic breed Dahlem Red. In native chicken; heterophil, lymphocyte, basophil, eosinophil and monocyte counts were not found to be significantly (p>0.05) different from the exotic breed, Dahlem Red. Plasma total proteins and albumin were found to be significantly (p0.05) for globulin was observed between the native and exotic breed, respectively.